PEMIMPIN DAN KEPIMIMPINAN DALAM LEMBAGA PENDIDIKAN - Musgar Musgar (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
The leader is a person who has skills and strengths, especially skills in one field, so he is able to influence other people to jointly carry out certain activities, for the sake of achieving one or several goals. The core of leadership is to influence others or subordinates, without subordinate leaders will not be able to be said as a leader. But the process of influence between leaders and subordinates is not unidirectional. The leaders are given the opportunity to exercise their influence based on expertise, attractiveness and legalistic status. But the authority of the leader will quickly vanish if it fails to give satisfaction to the expectations and needs of subordinates. A leader can direct, how to direct his subordinates to do the work in question towards a desired goal and target. Principal Personality and Training Affects Leadership. It is a fact that the individual brings something at work. Its strength, loyalty, and other personal and professional attributes will be significant factors that influence the type of leadership in school. Formal education institutions such as schools, Islamic boarding schools that are equal to recognized madrasas, are even accredited by the National Education Agency. Non-formal education institutions are family and community environment. By utilizing various public facilities owned by the community, for example mosques, prayer rooms, deliberation centers, houses of residents, and so on to carry out Islamic education. the word institution does not always refer to the definition of a building or organization that is formal in nature, but all forms of activities which contain values or rules can be called institutions.